Research in business education. Connecting research with the educational challenges of universities - Blanco-González, Alicia; Saavedra García, María Luisa; Cachón-Rodríguez, Gabriel; García Nistal, Alejandro (Journal of Management and Business Education, 2024)
Research in business education is crucial to address the challenges faced by universities. This research provides evidence to educators and policy makers for curriculum design and identifies best learning practices and helps to develop innovative teaching methods. The European Academy of Management and Business Economics (AEDEM), aware of the importance of contributing to the development of universities, created the Journal of Management and Business Education (JMBE). The aim of this research is to respond to the challenges that researchers are responding to and what are the future challenges in this field. To this end, a systematic analysis of 143 manuscripts published by the journal from its birth in 2018 to 2023 has been conducted. The results suggest important implications for researchers and how the main research themes in this field relate to the Sustainable Development Goals (SDGs).